2018
DOI: 10.1016/j.immuni.2018.04.007
|View full text |Cite|
|
Sign up to set email alerts
|

Transfer of Cell-Surface Antigens by Scavenger Receptor CD36 Promotes Thymic Regulatory T Cell Receptor Repertoire Development and Allo-tolerance

Abstract: The development of T cell tolerance in the thymus requires the presentation of host proteins by multiple antigen-presenting cell (APC) types. However, the importance of transferring host antigens from transcription factor AIRE-dependent medullary thymic epithelial cells (mTECs) to bone marrow (BM) APCs is unknown. We report that antigen was primarily transferred from mTECs to CD8α dendritic cells (DCs) and showed that CD36, a scavenger receptor selectively expressed on CD8α DCs, mediated the transfer of cell-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 54 publications
2
65
1
Order By: Relevance
“…TLR9/MyD88 signaling in mTECs recruits CD14 + moDCs. Chemokine-dependent migration of DCs to the proximity of mTECs, which underpins the mechanisms of CAT 18 , has been shown to be essential for the presentation of mTEC-derived antigens by DCs 6,10 . One prediction from the TEC-dependent TLR/MyD88-induced influx of Sirpα + cDC2 to the thymic medulla is that the frequency of CAT to this subset would be enhanced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TLR9/MyD88 signaling in mTECs recruits CD14 + moDCs. Chemokine-dependent migration of DCs to the proximity of mTECs, which underpins the mechanisms of CAT 18 , has been shown to be essential for the presentation of mTEC-derived antigens by DCs 6,10 . One prediction from the TEC-dependent TLR/MyD88-induced influx of Sirpα + cDC2 to the thymic medulla is that the frequency of CAT to this subset would be enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…mTECs mediate the promiscuous expression of thousands of otherwise strict tissuerestricted self-antigens (TRAs), a large number of which are under the control of the transcriptional regulator Aire 2 . The presentation of TRAs by mTECs can result in either the deletion of self-reactive T cells 3 or their conversion into Tregs 4,5 It has been recently demonstrated that the process of cooperative antigen transfer (CAT) from mTECs to DCs is essential for the establishment of thymic tolerance [6][7][8][9][10][11] . The complexity of CAT is foremost due to the heterogeneity of DCs in the thymus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FGF7 administration in GVHd mice has been shown to exert a protective effect on the thymic epithelium (10), and bone morphogenic protein 4 from thymic endothelial cells contributes to endogenous regeneration following thymic damage (11). Furthermore, medullary thymic epithelial cells can transfer host antigens to cd8α dendritic cells via cd36 to induce tolerance following allogenic BMT (12). FMS-like tyrosine kinase 3 ligand (FLT3) is a receptor tyrosine kinase homologous to c-Kit and c-fms and is expressed on hematopoietic progenitor cells.…”
Section: Co-transplantation Of Tonsil-derived Mesenchymal Stromal Celmentioning
confidence: 99%
“…The cDC1s efficiently mediate the cross-presentation of mTEC-derived pGE antigens and efficiently promote the generation of regulatory T cells (101). The scavenger receptor CD36 expressed by cDC1s facilitates the transfer of mTEC-derived self-antigens to cDC1s (102). The chemokine CCL21Ser, which is produced by an LTβR-dependent mTEC subpopulation (103), promotes the recruitment of cDC1 progenitors to the thymus (104).…”
Section: Hematopoietic Antigen-presenting Cellsmentioning
confidence: 99%